Poster: We Are Well: Seasonal Knowledges - Geraldine Burke; Priscilla Pettengell; Chris Hanger (2023)
The poster, ‘We Are Well: Seasonal Knowledges’ is part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. The poster showcases a range of flowers and plants such as chocolate lilies and wattle flowers that participants harvested and drew during Sept-Oct on Boon Wurrung land. The drawings lie on top of eco-dyed fabric where the colour dye is derived from the same plants during the same season. Poster text: I am a Youtuber. I learned that people can call on the wind and it will come, and that the wind carries soil. I liked learning about the thunder and lightning, taking my shoes off, and being outside. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Megan Adams, Nikki Browne, Aislinn Lalor, Chris Hanger Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr. Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists : Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara Elder. Founder of Yimba Yumba — in sync with nature through the art of sharing Wayapa Wuurrk, Kylie Colemane, Darug, and Wiradjuri First Nations consultant, artist, and educator. Founder of Your Green Prescription, Kursty Colemane, Darug, and Wiradjuri First Nations knowledge holder, artist, and educator.